Narrator of peace (Eurasian Journal of Philology Science and Education, 2016)
The article deals with creative work of Akhyt Ulimzhiuly Karymsakov, who lived in the second half of the ХІХ and the first half of the ХХ centuries, and left behind huge creative heritage. Several volumes of Akhyt’s heritage were published in China, Mongolia, Turkey and Kazakhstan. The poet opposed to the subordination in many of his poems and sang with his verses about people’s freedom. This side of the poet was interpreted in the article comparing with the poets of sorrowful times. Firstly, his poems are being analyzed from ideological and thematic point of view and also it has mentioned that he urged his straggler people from knowledge and science to struggle for the development of education and science also join the ranks of developed countries. The next peculiarity of the poet is that he wrote poems comparing good and evil, and raised the issue of how to glorify the good name of the person. In other words, his call to humanity, morality, goodness and beneficence on the concrete examples is being analyzed. And his poems became the object of the research, which refer to the execution of Muslim’s duties and obligations without violating the rules of Sharia. Akhyt is regarded as a religious enlightener.
Keywords: poetry; subordination; disagreement; freedom of the people; poets of sorrowful times; ideological thematic; humanity; morality; good of sorrowful times; goodness; beneficence; Muslim’s duties and obligations; reli